Effectiveness of optimising fetal positioning and birthing ball on the incidence of perineal tears in labouring mothers - Diana Khoirunniza; Nor Asiyah; Irawati Indrianingrum (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Perineal tears are one of the complications that often occur in normal childbirth and can cause pain, bleeding, and impaired recovery of postpartum women. Factors that influence the incidence of perineal tears include fetal position, elasticity of perineal tissue, and technique of delivery. Optimising Fetal Positioning (OFP) and the use of Birthing Ball are non-pharmacological interventions that aim to help optimal fetal positioning and improve pelvic mobility during labour. Purpose: This study aims to determine the effectiveness of Optimizing Fetal Positioning and Birthing Ball on the incidence of perineal tears in labouring women. Method: The study used a quasi-experimental design with a relational empirical approach. The study sample was 40 normal labouring women who were divided into two groups, 20 intervention group respondents and 20 control group respondents. Data were collected through observation of intervention implementation and examination of perineal conditions after delivery. Data analysis used the Chi-Square test. Results: The proportion of perineal tears in the intervention group was lower than the control group, but the statistical test results showed no statistically significant relationship (p-value > 0.05). Nevertheless, there was a tendency to decrease the incidence of perineal tears in mothers who received OFP and Birthing Ball interventions. Conclusion: The combination of Optimising Fetal Positioning and Birthing Ball is not statistically effective in reducing the incidence of perineal tears, but has the potential to provide clinical benefits. Suggestion: Future research is recommended to use a larger sample size and control for other confounding factors.